PENGARUH TEKNIK PROBING-PROMPTING TERHADAP KEMAMPUAN MEMECAHKAN MASALAH PADA PEMBELAJARAN FISIKA SISWA KELAS X SMA - Anggita Nova; Ernawati Saptaningrum; Joko Siswanto (Jurnal Penelitian Pembelajaran Fisika, 2015)
This research is motivated student of low ability in problem solving because students simply fixated on theory so difficult applied to real life. In learning physics concerning materials that occur naturally in the environment is not just a theory but delivered only link between the material being taught and the students in  real-world situations. Therefore need a solution in the form of innovation to improve students problem-solving skills. This study aims to determine the effect of techniques probing-prompting for problem-solving skills in learning physics class X SMA N 1 Juwana academic year 2014/2015 on the subject the Law of Archimedes. This study uses a pre-experimental research design with pretest-posttest form only control group design. Samples were taken by purposive sampling that is in class X Mia 2 as a single experimental class. Analysis of the initial data including normality test, while the final data analysis including normality test, hypothesis testing, gain test, and test indicators of problem-solving skills. After analysis it was found that the experimental class are normally distributed. The results of calculations based on the t test analysis obtained by value   tcount > t table that is 15.722 > 2.68 with a significance level of 5% with db = 36. Because tcount > t table then H0 is rejected and Ha is accept. From the results of t test analysis can be concluded that there are significant administration-prompting probing techniques for problem-solving skills in learning physics class X Semester 2 SMA N 1 Juwana on the subject of the law of Archimedes.